Macrofauna bivalve diversity from the deep northern Gulf of Mexico. Issue 2 (20th March 2020) - Wei, Chih‐Lin; Chen, Min; Wicksten, Mary K.; Rowe, Gilbert T.
Abstract: Abundance, α diversity, and faunal zonation of infaunal bivalve mollusks were measured along multiple depth transects in the deep northern Gulf of Mexico (GoM) covering depths of 213 to 3, 732 m. Density decreased exponentially from the shallow continental slope (0.2–1.0 km) down to the abyssal plain depths (3.0–3.7 km). Diversity increased down the slope to a maximum at intermediate depths (1.2 to 1.8 km), followed by a decrease down to the Sigsbee Deep. The maximum diversities coincided with an organic carbon input of 10 to 16.3 mg C m −2 d −1, whereas the minimum was encountered at the high (ca. 52–78 mg C m −2 d −1 ) and low extremes (ca. 3–5 mg C m −2 d −1 ) of the detrital food input. Seven faunal zones could be identified on the basis of species composition with faunal changes being more abrupt on the upper slope compared to the lower slope and abyssal plain, possibly due to steeper gradients in physical variables. Abstract : Abundance, diversity, and faunal zonation of infaunal bivalve mollusks were measured along multiple depth transects in the deep northern Gulf of Mexico. Density decreased exponentially from the shallow continental slope down to the abyssal plain depths. Diversity increased down the slope to a maximum at intermediate depths, followed by a decrease down to the Sigsbee Deep. Depth faunal zones could be identified on the basis of species composition with faunal changes being more abrupt on the upper slope compared to the lower slope and abyssal plain, possibly due to steeper gradients in physical variables.